Poverty and intellectual development in childhood - Roos, Leslie L.; Detillieux, Gilles; Fransoo, Gillian (International Journal of Population Data Science, 2025)
Introduction Childhood exposure to and duration of poverty can affect several individual characteristics related to intellectual development. Objectives This paper examines the implications of movement in and out of childhood poverty using a unique linkable database from the Canadian province of Manitoba. Differences in measurement of poverty and intellectual development are explored. Methods Almost 90,000 children were followed using two definitions of poverty -- neighborhood and household poverty. The large database permitted exploring the role of another variable -- maternal mental health. Results The association of household poverty with poorer intellectual outcomes has been shown to be stronger than the association of neighborhood poverty with such outcomes. This was true using various outcome measures appropriate across childhood (from age 5 to age 17). Comparisons with the role of maternal mental health were made and further analyses suggested. Conclusion The richness of the data has facilitated the study of childhood intellectual development. Household poverty appears to play an important role; neighborhood poverty and maternal mental health also seem to influence such development, but less strongly.